Pengelolaan Santri di Sekolah Menengah Atas Pondok Pesantren Modern Al-Ikhlas Lubuklinggau - Hamdan Hamdan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The aim of the study was to know the islamic boarding school students management in modern Islamic senior high school Al-Ikhlas Lubuklinggau. The method used was qualitative descriptive method. The results presented committees formation, brochures distribution, new students selection, students guidance, and students administration. The whole elements were organized well based on the function. In conclusion, students management include students input management, supervising, obeying the rules, the teaching methods (tilawah, tazkiyah and ta`limah). Keywords: Management, Student, Islamic Boarding School Students